Livelihood Opportunities and Its Impact on Women in The Rural Areas of Afghanistan - Sidiqi, Shir Alam (Integrated Journal for Research in Arts and Humanities, 2023)
If women in rural areas have access to land, technology, financial services, education and markets like men, agricultural and non-agriculture (industry & services) production can be increased significantly, and the number of poor can be significantly reduced and impact the wellbeing of women in the rural areas. This paper aims to identify the possible livelihood opportunities for the poor people in the rural areas of Afghanistan, considering the current situation of the country, it requires to bring back at the center of focus to study the feasible livelihood opportunities and how it impacts the wellbeing of women in the rural areas of Afghanistan. Household headed women are in dire need in the rural areas of Afghanistan particularly after the collapse of the republic government after some of the restrictions were imposed on women. For analyzing the primary data model will be used for analyzing to determine the relationship between livelihoods opportunities and women lives in agricultural sector in rural areas of Afghanistan.